2012
DOI: 10.1128/iai.05680-11
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Infection Inhibits Th17-Mediated Spontaneous Development of Arthritis in Interleukin-1 Receptor Antagonist-Deficient Mice

Abstract: ABSTRACTInterleukin 1 receptor antagonist (IL-1Ra)-deficient BALB/c mice develop spontaneous arthritis resembling human rheumatoid arthritis. We herein report that infection withToxoplasma gondii, an intracellular protozoan, is capable of ameliorating the spontaneous development of arthritis in IL-1Ra-deficient mice. The onset of arthritis develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Additionally, transcriptional analysis of Batf3 -dependent DC in the mesLN and spleen revealed a significant increase in Il12b expression in mesLN DC but not splenic DC post-infection (Figure S6L) . Although we cannot completely exclude the possibility of a transient and discrete contribution of the BM, our present results, in agreement with previous studies (Oldenhove et al, 2009; Washino et al, 2012), support the idea that the MALT is the dominant source of early IL-12 following per-oral T. gondii infection.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, transcriptional analysis of Batf3 -dependent DC in the mesLN and spleen revealed a significant increase in Il12b expression in mesLN DC but not splenic DC post-infection (Figure S6L) . Although we cannot completely exclude the possibility of a transient and discrete contribution of the BM, our present results, in agreement with previous studies (Oldenhove et al, 2009; Washino et al, 2012), support the idea that the MALT is the dominant source of early IL-12 following per-oral T. gondii infection.…”
Section: Resultssupporting
confidence: 91%
“…Previously, we showed that Th1 cells are preferentially differentiated in T. gondiiinfected mice (17). In these mice, Th17 cell differentiation is suppressed, consistent with the observation that Th17 cell differentiation and Th1 cell differentiation are mutually suppressive (18).…”
supporting
confidence: 87%
“…T. gondii infection may not always be deleterious. For example, it inhibits the development of arthritis in mice deficient in the interleukin receptor antagonist (IL1RN) [106]. T. gondii infection is also able to reduce infarct size in focal cerebral ischaemia in mice, an effect attributed to the ability of infection to increase the expression of nerve growth factor, as well as that of anti-inflammatory cytokines and of glutathione and oxidative stress protective genes, while reducing the expression of proinflammatory cytokines [107].…”
Section: Resultsmentioning
confidence: 99%